1994
DOI: 10.1055/s-0038-1648920
|View full text |Cite
|
Sign up to set email alerts
|

Release of Tissue-Type Plasminogen Activator in Response to Muscarinic Receptor Stimulation in Human Forearm

Abstract: SummaryWe have recently shown that mental stress increases local net release of tissue-type plasminogen activator (t-PA) across the forearm vascular bed. However, the mechanisms responsible for the t-PA release in man during stress are undefined. To study the effects of endothelial cell receptor stimulation and fluid shear stress we used the perfused forearm model to characterize the in vivo tissue plasminogen activator (t-PA) response in man to methacholine (Mch) and sodium nitroprus-side (SNP), at doses calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 24 publications
5
33
0
Order By: Relevance
“…18 Our finding that this com- pound failed to stimulate t-PA release reinforces the concept that the relationship between NO and fibrinolysis mainly occurs within endothelial cells. Although evidence is concordant on the possibility to release t-PA by receptor-operated agonists, including methacholine 15,17 and bradykinin, 16,19 results with acetylcholine are discordant. 16,19 However, a likely explanation is the short duration of acetylcholine infusion in negative articles (5 minutes per dose) 16 as compared with our experimental conditions (15 minutes per dose).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Our finding that this com- pound failed to stimulate t-PA release reinforces the concept that the relationship between NO and fibrinolysis mainly occurs within endothelial cells. Although evidence is concordant on the possibility to release t-PA by receptor-operated agonists, including methacholine 15,17 and bradykinin, 16,19 results with acetylcholine are discordant. 16,19 However, a likely explanation is the short duration of acetylcholine infusion in negative articles (5 minutes per dose) 16 as compared with our experimental conditions (15 minutes per dose).…”
Section: Discussionmentioning
confidence: 99%
“…Because sodium nitroprusside administration, despite a similar blood flow increment, had no such effect, these results confirm that the t-PA release is an endothelial property not dependent on flow increase. [15][16][17] Worth noting, sodium nitroprusside is an exogenous NO donor, acting directly on vascular smooth muscle cells. 18 Our finding that this com- pound failed to stimulate t-PA release reinforces the concept that the relationship between NO and fibrinolysis mainly occurs within endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial release of t-PA may be regulated in part by nitric oxide (Jern et al 1994;Newby et al 1998). Hoetzer et al (2003a) found a dose dependent increase in t-PA antigen net release in response to bradykinin.…”
Section: Fibrinolytic Potentialmentioning
confidence: 99%
“…This may not be surprising since both endothelial function and Wbrinolytic potential are at least partially regulated by nitric oxide (Jern et al 1994;Newby et al 1998) and aerobic exercise is thought to improve nitric oxide metabolism (Kingwell et al 1997). While resistance exercise is strongly recommended as part of a regular exercise program, little is known about the eVects of resistance training on either endothelial function or Wbrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the systemic levels of tPA may not reflect the local profibrinlolytic capacity in terms of availability of active tPA at the organ level. In 1994 we therefore described a human in vivo model, in which the release of fibrinolytic proteins from the endothelium could be studied in man [7–9].…”
Section: Introductionmentioning
confidence: 99%